Liver mesenchymal stem cells are superior inhibitors of NK cell functions through differences in their secretome compared to other mesenchymal stem cells - Yigitbilek, Furkan; Ozdogan, Elif; Abrol, Nitin; Park, Walter D.; Hansen, Michael J.; Dasari, Surendra; Stegall, Mark D.; Taner, Timucin (Frontiers in Immunology, 2022)
Liver-resident mesenchymal stromal cells (L-MSCs) are superior inhibitors of alloreactive T cell responses compared to their counterparts from bone marrow (BM-MSCs) or adipose tissue (A-MSCs), suggesting a role in liver’s overall tolerogenic microenvironment. Whether L-MSCs also impact NK cell functions differently than other MSCs is not known. We generated and characterized L-MSCs, A-MSCs and BM-MSCs from human tissues. The mass spectrometry analysis demonstrated that L-MSC secretome is uniquely different than that of A-MSC/BM-MSC, with enriched protein sets involved in IFNγ responses and signaling. When co-cultured with primary human NK cells, L-MSCs but not other MSCs, decreased surface expression of activating receptors NKp44 and NKG2D. L-MSCs also decreased IFNγ secretion by IL-2-stimulated NK cells more effectively than other MSCs. Cytolytic function of NK cells were reduced significantly when co-cultured with L-MSCs, whereas A-MSCs or BM-MSCs did not have a major impact. Mechanistic studies showed that the L-MSC-mediated reduction in NK cell cytotoxicity is not through changes in secretion of the cytotoxic proteins Perforin, Granzyme A or B, but through increased production of HLA-C1 found in L-MSC secretome that inhibits NK cells by stimulating their inhibitory receptor KIRDL2/3. L-MSCs are more potent inhibitors of NK cell functions than A-MSC or BM-MSC. Combined with their T cell inhibitory features, these results suggest L-MSCs contribute to the tolerogenic liver microenvironment and liver-induced systemic tolerance often observed after liver transplantation.